Belief and ageing : Spiritual pathways in later life - Coleman, Peter G. (Book collections on Project MUSE., 2011)
This book illustrates the variety of religious, spiritual and other beliefs held by older people, including British Christians, Muslims, Humanists and witnesses of the Soviet persecution of religion.